Students’ Grammatical Mistakes on the Use of Language Features in Composing Narrative Text - Heriyanti Tahang; Yuliana A; Emiliana Oratmangun; Syahira Syahira; Shoheh Shoheh (JLE: Journal of Literate of English Education Study Program, 2024)
A narrative text with several grammatical and linguistic aspects is one of the texts learned in senior high school. In fact, according to the researcher's prior observation, students faced numerous challenges when attempting to write it, especially grammatical mistakes in using language features. This study aims to detect grammatical errors in the utilization of language elements in narrative texts produced by students, as well as to determine the underlying reasons contributing to these errors. The recent research employed a descriptive qualitative methodology. Eight of the eleventh-grade students studying Online Business and Marketing major in SMK Negeri 1 Kota Sorong have been selected as the participants in this research. Due to the COVID-19 pandemic situation which restricted social interactions, only those students than could be reached out to gather data. The data was derived from a writing exam and a semi-structured interview. Upon analyzing the student's writing, it was discovered that they made errors in utilizing the simple past tense and action verbs. Simultaneously, the interview data indicated that the causes contributing to grammatical errors in using language features in this study were limitations, lack of attention, and carelessness. This research finding implied that the teacher must identify the most effective technique to engage the student's attention and enable them to concentrate on acquiring language skills for future use in creating narrative texts.